MENINGKATKAN KUALITAS GURU MELALUI PENDIDIKAN PROFESI GURU - -, Sutoyo (UNIVERSITAS SLAMET RIYADI, 2014)
The education of Teachers Profession (PPG) both during its position and pre-position is conducted to improve the quality and welfare of teachers. However, its implementation makes some problems; 1) problem with certification, 2) those graduation who cannot continue to PPG, 3) the unbalance of graduation and those accomodated to PPG, 4) the quality and distribution of LPTK, 5) the cooperation between LPTK and the local government, 6) the problem of mindset changing. In spite of its various problems, The education of Teachers Profession (PPG) must be conducted based on its early goal, preparing teachers with its competence related to National Education Standard. Â Â Keywords: teachers' quality, The education of Teachers Profession (PPG)